Policy review on the management of pre-eclampsia and eclampsia by community health workers in Mozambique - Salésio Macuácua; Raquel Catalão; Sumedha Sharma; Anifa Valá; Marianne Vidler; Eusébio Macete; Mohsin Sidat; Khátia Munguambe; Peter von Dadelszen; Esperança Sevene; the CLIP Working Group (BMC, 2019)
Abstract Background Pre-eclampsia is one of the leading causes of maternal death in Mozambique. Limited access to health care facilities and a lack of skilled health professionals contribute to the high maternal morbidity and mortality rates in Mozambique and indicate a need for community-level interventions. The aim of this review was to identify and characterise health policies related to the role of CHWs in the management of pre-eclampsia and eclampsia in Mozambique. Methods The policy review was based on three methods: a desk review of relevant documents from the Mozambique Ministry of Health (n = 7), contact with 28 key informants in the field of health policy in Mozambique (n = 5) and literature review (n = 699). Policy documents obtained included peer-reviewed articles, government and institutional policies, reports and action plans. Seven hundred and eleven full-text documents were assessed for eligibility and included based on pre-defined criteria. Qualitative analysis was done to identify main themes using content analysis. Results A total of 56 papers informed the timeline of key events. Three main themes were identified from the qualitative review: establishment of the community health worker programme and early challenges, revitalization of the CHW programme and the integration of maternal health in the community health tasks. In 1978, following the Alma Alta Declaration, the Mozambique government brought in legislation establishing primary health care and the CHW programme. Between the late 1980s and early 1990s, this programme was scaled down due to several factors including a prolonged civil war; however, the decision to revitalise the programme was made in 1995. In 2010, a revitalised programme was re-launched and expanded to include the management of common childhood illnesses, detection of warning signs of pregnancy complications, referrals for maternal health and basic health promotion. To date, their role has not included management of emergency conditions of pregnancy including pre-eclampsia and eclampsia. Conclusion The role of CHWs has evolved over the last 40 years to include care of childhood diseases and basic maternal health counselling. Studies to assess the impact of CHWs in providing services to reduce maternal morbidity and mortality are recommended.